KUALITAS PELAYANAN ADMINISTRASI KEPENDUDUKAN DI DESA BOU KECAMATAN LAMBANDIA KABUPATEN KOLAKA TIMUR - Akbar Sabiruddin; Patta Hindi Asis; Yunitawati Lampasa; Darwan Sari; Muhammad Ihsan Mattalitti; Andi Awaluddin Ma’ruf (Journal Publicuho, 2024)
This study analyses the quality of public administration services in population administration in Bou Village, Lambandia District, East Kolaka Regency. Using a descriptive qualitative approach, this research aims to explore the factors influencing the quality of public services in the village, with a particular focus on essential administrative processes for residents. Data were collected through direct interviews and observations involving six informants, including village officials and community members. The results indicate that Desa Bou has made efforts to improve public service quality but faces several challenges. The Tangibles dimension lacks adequate facilities, such as breastfeeding rooms and disability-friendly services. Reliability is hindered by the absence of clear SOPs, leading to procedural inconsistencies. Responsiveness and Courtesy are rated positively, as village officials are attentive and friendly. However, issues remain in Competence, with limited training for staff affecting service efficiency.